Synthesis and Characterization of Novel Polyimides Based on 2,6-bis(m-Amino Phenoxy) Benzoyl Naphthalene - (:unkn) unknown (AIDIC SERVIZI SRL, 2013)
It is well known that aromatic polyimides (PIs) have found wide applications in many industrial fields due to their excellent thermal stability, high mechanical strength, high stability to ionizing, good film forming ability, and superior chemical resistance. In this work we synthesized a novel monomer containing naphthalene, 2,6-Bis(m-amino phenoxy) benzoyl naphthalene. A series of novel polyimide based on 2,6-Bis(m-amino phenoxy) benzoyl naphthalene were prepared. FTIR was used to identify the novel synthesized monomer and polyimides. Polyimides were synthesized via the known two-step process; preparation of poly(amic-acid) in DMAc, followed by thermal imidization. TGA was used to measure the thermal properties. Mechanical properties of the free films were determined by standard tensile stress-strain tests.
Keywords: KINETICS